2012
DOI: 10.1542/peds.2011-3587
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Type Human Papillomavirus and Evidence of Herd Protection After Vaccine Introduction

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Clinical trials have demonstrated that prophylactic human papillomavirus (HPV) vaccines are highly effective in preventing HPV infection, but the impact of vaccination on HPV prevalence rates in real-world, community settings is uncertain. WHAT THIS STUDY ADDS:This study provides evidence of a substantial decrease in the prevalence of vaccine-type HPV among young women and evidence of herd protection in a community only 4 years after the quadrivalent HPV vaccine was licensed.abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 37 publications
7
97
0
1
Order By: Relevance
“…These findings are consistent with results from the studies in the United States and other countries that may reflect early vaccine impact (8)(9)(10)(11)(12). For example, Australia has observed dramatic declines in genital warts among women under 21 years of age from 18.6% to 1.9% during 2007 to 2011 and in high-grade cervical abnormalities among women under 18 years of age from 0.80% to 0.42% before and after 2007 (10,11).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are consistent with results from the studies in the United States and other countries that may reflect early vaccine impact (8)(9)(10)(11)(12). For example, Australia has observed dramatic declines in genital warts among women under 21 years of age from 18.6% to 1.9% during 2007 to 2011 and in high-grade cervical abnormalities among women under 18 years of age from 0.80% to 0.42% before and after 2007 (10,11).…”
Section: Discussionsupporting
confidence: 86%
“…Bauer and colleagues showed a 35% decrease in genital warts among women younger than 21 years of age (from 0.94%-0.61%) between 2007 and 2010 using a family planning administrative database in California (8). Kahn and colleagues estimated a reduction in prevalence of vaccine-type HPV infections from 32% to 13% during 2006 to 2010 among young women recruited from primary care clinics (9). Similar findings have been reported from other countries (10)(11)(12).…”
Section: Introductionsupporting
confidence: 57%
“…[16][17][18] Race was defined as black, white, or other, and ethnicity was defined as Hispanic and non-Hispanic. Each woman also provided a cervicovaginal swab for HPV DNA testing, which was performed using the Roche Linear Array Assay, a PCR amplification/detection system that uses pooled L1 primers and a reverse-line blot detection step to identify 36 different HPV genotypes (Roche Molecular Systems, Alameda, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Black women were more likely than white women to be positive for ‡1 HPV type (odds ratio [OR] 1.83, 95% CI 1.30-2.58) and Hispanic women were less likely than non-Hispanic women to be positive for ‡1 HPV type (OR 0.47, 95% CI 0.24-0.92). However, among all young women and HPV-infected women, neither race nor ethnicity was associated with positivity for HPV types targeted by the following vaccines: 2-valent (HPV16 and/or 18), 11,16,and/or 18),11,16,18, 31, 33, 45, 52, and/or 58). Conclusion: The prevalence of HPV types targeted by the 2-valent, 4-valent, and 9-valent vaccines did not differ by race or ethnicity among all and among HPV-infected women in this sample.…”
Section: Introductionmentioning
confidence: 91%
“…12 The quadrivalent HPV (6/11/16/18) virus-like particle (qHPV) vaccine is highly efficacious in preventing infection and cervical, vaginal, vulvar, and anal dysplasia caused by HPV 6/11/16/18 as well as HPV 6/11-related condyloma, [13][14][15][16] and the bivalent HPV (16/18) vaccine is highly efficacious against HPV 16/18-related infection and cervical dysplasia. 17 Postlicensure studies have shown a rapid decrease in the incidence of high-grade cervical abnormalities, [18][19][20][21] prevalence of vaccine HPV types, [22][23][24][25][26] and incidence of genital warts [27][28][29][30][31] in vaccinees. Data have shown that prophylactic HPV vaccination is generally safe and well tolerated.…”
Section: What This Study Addsmentioning
confidence: 99%